Multidimensional Patterns of Primary School Students’ Difficulties in Solving Higher-Order Thinking Problems on Mixed Arithmetic Operations - Sarmilah; Indrie Noor Aini; Rina Marlina (Program Studi Pendidikan Matematika, Universitas Majalengka, 2026)
The integration of higher-order thinking skills (HOTS) into primary mathematics education requires students to engage in complex reasoning; however, many students continue to experience significant difficulties, particularly when solving problems involving mixed arithmetic operations. This study aims to analyze the multidimensional patterns of students’ difficulties by examining cognitive, affective, and pedagogical factors that influence their problem-solving processes. A qualitative descriptive design was employed, involving one mathematics teacher and three primary school students representing high, medium, and low achievement levels. Data were collected through document analysis, questionnaires, classroom observations, and in-depth interviews, and analyzed using thematic analysis with triangulation across data sources. The findings reveal that students’ difficulties are inherently multidimensional. Cognitively, students demonstrate fragmented reasoning and limited relational understanding, relying on procedural strategies without fully integrating conceptual structures. Affectively, cognitive overload, anxiety, and low confidence reduce students’ persistence and lead to avoidance behaviors such as guessing. Pedagogically, the dominance of procedural instruction and limited exposure to HOTS-oriented tasks contribute to algorithmic dependency and restrict the development of flexible problem-solving strategies. These dimensions interact dynamically, forming a reinforcing cycle that hinders students’ ability to engage effectively with complex mathematical tasks. This study contributes to the field by proposing a multidimensional analytical framework that integrates cognitive, affective, and pedagogical perspectives in understanding students’ mathematical difficulties. The findings highlight the need for instructional approaches that simultaneously support conceptual understanding, manage cognitive load, and foster positive affective engagement. Such approaches are essential for enhancing students’ higher-order thinking skills and improving the quality of mathematics learning in primary education